Nursing research priorities based on CINAHL database: A scoping review - Hanna Hopia; Johanna Heikkilä (Wiley, 2020)
Abstract Aim To analyse nursing research based on the CINAHL database to identify research priorities for nursing. Design A scoping literature review was conducted. The CINAHL Plus (EBSCO) Full Text was searched between 2012-2018. Methods Out of 1522 original publications, 91 fulfilled the inclusion criteria. The Joanna Briggs Institute critical appraisal tools were applied. Data were analysed by a thematic analysis method. Results A strong emphasis should be put on development and evaluation of nursing theories and, in addition, randomized controlled trial studies, meta‐synthesis, experimental and intervention studies are needed in nursing research. Development of competencies and skills in the nursing profession ought to be studied more extensively and research should be focused on variety fields of nursing practice.